Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M.; Morcuende, D.; Ramírez, R.; Ventanas, J.; Cava, R. (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
The following values have no corresponding Zotero field: accession-num: 22061520
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs

Extensively reared Iberian pigs versus intensively reared white pigs for the manufacture of liver pâté. - Estévez, M; Morcuende, D; Ramírez, R; Ventanas, J; Cava, R (Meat science, 2004)
Physico-chemical characteristics and quality traits of the raw ingredients (muscle cuadriceps femoris, liver and adipose tissue) and the pâtés made from extensively reared Iberian pigs and intensively reared white pigs, were evaluated. The differences found between muscles, livers and adipose tissues from Iberian and white pigs influenced the characteristics of the pâtés. Compared to pâtés from white pigs, pâtés from Iberian pigs had a higher content of heme iron (27.5 μg/g vs 11.5 μg/g; p<0.05) and lower content of non-heme iron (27.5 μg/g vs 33.7 μg/g; p<0.05). Pâtés from Iberian pigs exhibited a darker colour (L (∗):18.6 vs 15.9, p<0.05) with less redness (a (∗) values: 9.1 vs 11.3; p<0.05) and yellowness (b (∗) values: 13.1 vs 14.8, p<0.05). Thus, pâtés from white pigs had higher values of chroma (18.6 vs 15.9, p<0.05) and smaller values of hue (52.5 vs 55.2, p<0.05) that those from Iberian pigs' pâtés. In fatty acid composition, pâtés from white pigs had higher proportions of SFA (37.9% vs 32.8%, p<0.05) and PUFA (14.4% vs 9.6%, p<0.05) than pâtés from Iberian pigs and lower percentages of oleic (53.4% vs 43.6%, p<0.05) and total of MUFA (57.5% vs 47.6%, p<0.05). Pâtés from Iberian pigs had a lower n-6/n-3 values (13.2 vs 17.2; p<0.05).
Keywords: Extensive; fatty acids; Iberian pigs; Instrumental colour; Iron; liver p; liver paté; White pigs

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution